PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP BELANJA MODAL - Nurzen, Miardi; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the economic growth, Local Own-Source Revenue, and General AllocationFund has an influence to the Capital Expenditure at the Districts /Cities Government in East Java. Thepopulation of this research is the entire of districts /cities in the area of East Java Province. The data usessecondary data which has been retrieved from the Districts / Cities Realization Budget Report in East JavaProvince from 2012 to 2014. The data analysis instrument has been done by using multiple linear regressionsanalysis. Based on the test it shows that: 1) the economic growth does not have any influence to the CapitalExpenditure; 2) The Local Own Source Revenue has positive influence to the Capital Expenditure; 3) GeneralAllocation Fund has positive influence to the capital expenditure.Keywords: Economic Growth (PE), Local Own Source Revenue (PAD), General Allocation Fund (DAU),capital expenditure (BM).